Phase separation in polycrystalline Pr0.5Sr0.5−xCaxMnO3 - Niebieskikwiat, Dario Gabriel (2001)
In this work we present electrical resistivity and magnetization (M) data as a function of temperature T and magnetic field H of polycrystalline Pr0.5Sr0.5−xCaxMnO3 (x = 0.1 and 0.2). Within a large T range we have observed the coexistence of the ferromagnetic (FM) and charge-ordered antiferromagnetic phases. From the spontaneous magnetization in the M(H) curves we obtained the fraction of the FM phase XFM. We found that XFM is ˜20% at low T, and increases by increasing both T and H. Through a simple free-energy model driven by random disorder, we reproduce the T and H evolution of the phase-separation phenomena. We also show that a low-energy difference between the competing states is responsible for the dramatic effects that the disorder has on the physical properties.